Cerebral Dopamine Neurotrophic Factor Diffuses Around the Brainstem and Does Not Undergo Anterograde Transport After Injection to the Substantia Nigra - Albert, Katrina; Renko, Juho-Matti; Mätlik, Kert; Airavaara, Mikko; Voutilainen, Merja H. (Frontiers in Neuroscience, 2019)
Cerebral dopamine neurotrophic factor (CDNF) has shown therapeutic potential in rodent and non-human primate models of Parkinson’s disease by protecting the dopamine neurons from degeneration and even restoring their phenotype and function. Previously, neurorestorative efficacy of CDNF in the 6-hydroxydopamine (6-OHDA) model of Parkinson’s disease as well as diffusion of the protein in the striatum (STR) has been demonstrated and studied. Here, experiments were performed to characterize the diffusion and transport of supra-nigral CDNF in non-lesioned rats. We injected recombinant human CDNF to the substantia nigra (SN) of naïve male Wistar rats and analysed the brains two, six, and twenty-four hours after injections. We performed immunohistochemical stainings using an antibody specific to human CDNF and radioactivity measurements after injecting iodinated CDNF. Unlike the previously reported striatonigral retrograde transport seen after striatal injection, active anterograde transport of CDNF to the STR could not be detected after nigral injection. There was, however, clear diffusion of CDNF to the brain areas surrounding the SN, and CDNF colocalized with tyrosine hydroxylase (TH)-positive neurons. Overall, our results provide insight on how CDNF injected to the SN may act in this region of the brain.